Research of sales dynamics of body wieght regulation means in ukraine - Притульська, Наталія Володимирівна; Сєногонова, Галина Ігорівна (Technology audit and production reserves, 2014)
The problem of overweight was revealed in the paper. In total, about 15% of our population suffers from obesity. Obesity should be treated as a chronic disease, and like any chronic disease, it requires long-term treatment under medical supervision. Low information culture of the population and sometimes lack of doctors' attention to this problem has led to the fact that different body weight regulation means, most of which are naturally BAAs (biologically active additives) have become widespread in Ukraine recently. With the support of a marketing group “Business-credit”, market research of sale of foreign weight regulation means was conducted. It was aimed at identifying the main distribution channels of these products and giving a brief characteristic of the most common means as well. The main reason for this study was the variety of products for weight regulation. It was tasked to identify the most popular means, conduct comparative analysis of prices for means in different places of sale, estimate the costs of purchasing a particular product in combination with its expiration date and briefly describe the most popular means. The data show that biologically active substances are the most popular weight regulation means. Over the last year, an increase in sales of foreign bioactive substances has decreased by 22.74% while the increase in sales of domestic bioactive substances has grown by 64.17%. The situation is caused by the difference in price: domestic biologically active substances are on average 27.38 USD cheaper than foreign.